Analysis of Time-Use Pattern Among Rural and Urban Women In Ondo State, Nigeria - Osuji, Joy Adaeze; Obisesan, Adekemi A. (Journal of Science, Technology and Innovation Research, 2025)
Multi-tasking and lack of time saving infrastructure also subject women in the developing world to time pressure since they are engaged in reproductive, productive and community chores. This research examines how the rural and urban women in Ondo State, Nigeria spend their time. These particular goals were to explain socio-economic attributes of respondents, compare their time use habits, and determine the primary challenges of time management. A multistage sampling technique was used in the selection of respondents, which involves the random selection of four LGAs, ten communities, and 15 respondents per community, giving a total sample size of 150 women (75 urban and 75 rural). A well-structured copies of questionnaires was used to collect primary data from rural and urban women. Descriptive and inferential statistics were used to analyze the data collected. The results showed an average age of (36.1) years with rural women being older than urban women, (55.3%) were married and (85.3%) were employed while rural women were primarily in agriculture. Urban women were more educated (54.7%) and recorded higher incomes (11,433.10) than rural women. Majority (64.7%) of the urban women are members of the co-operative society while few of the rural women respondents (34.7%) were members of cooperative societies. The results showed that majority (90.7%) of the rural women do not have access to time-saving technology while (56.0% ) of the rural women had access to time saving technology. The majority (85.3%) of the urban women used gas for cooking, while (69.3%) of the rural women relied on firewood. Furthermore, urban women spent an average of 15.7 hours/day on various activities, while rural women spent a mean of 16.64 hours/day on various activities, with the overall mean of 16.17 hours/day on various activities indicating increased fatigue and stress on rural women. There were significant differences in the time spent on domestic chores, wage employment, and family business. Urban women spent slightly more time on ironing and child care while rural women spent significantly more time fetching firewood and water. In urban areas, women enjoy the comfort of electricity and time saving gadgets whereas in rural areas, women are more time strained because of poor infrastructure, multi occupational status and the high volume of unpaid labor. All the respondents lacked skills in time management. Finally, the research paper suggests that special interventions such as enhancement of rural infrastructure, access to clean cooking energies, water, and economic empowerment initiatives are necessary to save time and enhance the wellbeing of women, particularly in the rural regions.